Death and Afterlife in Ancient Israel and the Hebrew Bible - Garroway, Kristine Henriksen (Currents in biblical research, 2025)
Since the decipherment of hieroglyphics and cuneiform, scholars of the ancient Near East and Hebrew Bible have debated the ways in which the afterlife in ancient Israel compared to that of its neighbors. The debate focuses on how unique Israelite afterlife views really were. Older questions surrounding cults of the dead have been met with newer questions examining purity and impurity in burials, the place of women and children in the afterlife, and how grave goods functioned. The current consensus is that Israel had similar, but distinct practices that welcomed the entire family into a cult of the dead kin.